Investigation of Possible Correlation between Giardia duodenalis Genotypes and Clinical Symptoms in Southwest of Iran - RAFIEI, Abdollah (Tehran University of Medical Sciences, 2013)
BACKGROUND: Giardia duodenalis is one of the most important human enteric parasites throughout the world. Clinical symptoms of this parasite vary from asymptomatic infection to chronic diarrhea. Still it is not clear, whether different types of pathogenesis are due to different strains of organism or to variable host factors. The purpose of this study was to investigate possible correlation of clinical symptoms with assemblages among symptomatic and asymptomatic cases collected from southwest of Iran. METHODS: Fecal samples were collected from 100 symptomatic and asymptomatic cases, which were positive for G. duodenalis. The samples were subjected to semi-nested PCR and RFLP for gdh gene. RESULTS: Among symptomatic patients, 54% had mixed genotypes AII and BIII, 28% and 18% of samples indicated assemblages BIII and AII, respectively. In contrast, among asymptomatic cases, 64%, 26% and 10%samples had mixed genotypes, BIII and AII assemblages, respectively. Statistical analysis using Chi- Square test showed that there was no significant correlation between assemblage and clinical symptoms in current study. CONCLUSION: High prevalence of mixed infection in both groups may affect this conclusion, therefore further study in more details are necessary to clarify these finding. Additionally, it is important to carry out investigations regarding human host factors as well.